2006
DOI: 10.1016/j.cell.2006.06.025
|View full text |Cite
|
Sign up to set email alerts
|

OPA1 Controls Apoptotic Cristae Remodeling Independently from Mitochondrial Fusion

Abstract: Mitochondria amplify activation of caspases during apoptosis by releasing cytochrome c and other cofactors. This is accompanied by fragmentation of the organelle and remodeling of the cristae. Here we provide evidence that Optic Atrophy 1 (OPA1), a profusion dynamin-related protein of the inner mitochondrial membrane mutated in dominant optic atrophy, protects from apoptosis by preventing cytochrome c release independently from mitochondrial fusion. OPA1 does not interfere with activation of the mitochondrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

61
1,444
9
11

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,456 publications
(1,525 citation statements)
references
References 57 publications
61
1,444
9
11
Order By: Relevance
“…Two recent studies by Scorrano and de Strooper group have shed light on the possible mechanism of cristae remodeling during cell death through the fusion protein Opa1 [96,131]. Opa1 is processed from the long membrane anchored form of Opa1 (l-Opa1) to a soluble short form (s-Opa1).…”
Section: Mitochondrial Cristae Structure and Cell Death: Demolition Fmentioning
confidence: 99%
“…Two recent studies by Scorrano and de Strooper group have shed light on the possible mechanism of cristae remodeling during cell death through the fusion protein Opa1 [96,131]. Opa1 is processed from the long membrane anchored form of Opa1 (l-Opa1) to a soluble short form (s-Opa1).…”
Section: Mitochondrial Cristae Structure and Cell Death: Demolition Fmentioning
confidence: 99%
“…This protocol describes how to obtain functional, purified, intact mitochondria from three different sources: liver 16 , skeletal muscle 17 and cultured cells 18 . These variants intend to be exemplificative and not exhaustive, as they do not cover the different sources from which mitochondria can be isolated.…”
Section: Introductionmentioning
confidence: 99%
“…We and others have shown that OPA1 is a good candidate for the regulation of the cristae structure in the mitochondria. 11,14 Indeed, downregulation of OPA1 affect the IMM structure and integrity, leading to respiration defects and DC m loss, fission of the mitochondrial network, impairment of growth and apoptosis 11,[14][15][16][17][18] and OPA1 overexpression protects from cyt c mobilization by tightening cristae junctions. 14 OPA1 is also partially associated to the OMM, on its IMS side, where it might interact with Mfn1 to promote fusion of the mitochondrial network, or maintain a physical link between the OMM and IMM.…”
mentioning
confidence: 99%